Effect of CO2 and Nd:YAG Lasers on Shear Bond Strength of Resin Cement to Zirconia Ceramic - Shahin Kasraei; Loghman Rezaei-Soufi; Ebrahim Yarmohamadi; Amanj Shabani (Frontiers in Dentistry, 2016)
Objectives: Because of poor bond between resin cement and zirconia ceramics, laser surface treatments have been suggested to improve adhesion. The present study evaluated the effect of CO2 and Nd:YAG lasers on the shear bond strength (SBS) of resin cement to zirconia ceramic.